Inhibitory effect of melatonin on gonadotropin-releasing hormone-induced Ca2+ oscillations in pituitary cells of newborn rats - Zemková, H; Vanĕcek, J (Neuroendocrinology, 1997)
The effect of melatonin on the gonadotropin-releasing-hormone (GnRH)-induced oscillatory rises in intracellular calcium concentration, [Ca2+]i, was studied in cultured cells from the anterior pituitary gland of 6- to 8-day-old rats. GnRH-induced [Ca2+]i oscillations were recorded indirectly by monitoring the activity of apamin-sensitive Ca(2+)-activated K+ channels using the perforated patch-clamp technique and fast microperfusion system. Melatonin (1 nM) inhibited the initiation or attenuated the amplitude of oscillatory current responses induced by 10 nM GnRH in 72% of GnRH-sensitive cells. Analysis of the melatonin dose-inhibition relationship showed that melatonin inhibited the initiation of [Ca2+]i oscillations with IC50 = 0.35 nM. In partially inhibited cells, melatonin reduced the GnRH-induced current amplitude by 55% on the average, prolonged the delay in onset of response to GnRH and decreased the frequency of oscillations. Once initiated by GnRH, the amplitude and frequency of oscillatory currents was inhibited by melatonin after a latency of 10-30 s. These effects of melatonin were fully reversible. After pretreatment of neonatal gonadotropes with pertussis toxin, no inhibition by melatonin was observed. The inhibitory effect of melatonin on initiation, amplitude and frequency of GnRH-induced oscillatory current persisted in the absence of external Ca2+. Melatonin alone did not induce any transmembrane current or membrane potential changes. These observations suggest that melatonin reduces GnRH-induced calcium mobilization from intracellular stores.
Keywords: Rats; novorozená zvířata; melatonin; vápník; Gonadotropin-Releasing Hormone; Animals; Calcium; hormon uvolňující gonadotropiny; Dose-Response Relationship, Drug; Animals, Newborn; zvířata; Pituitary Gland; metoda terčíkového zámku; krysa rodu Rattus; vztah mezi dávkou a účinkem léčiva; ženské pohlaví; Female; hypofýza; Patch-Clamp Techniques; Melatonin